"Fixing" Climate Change by Mortgaging the Future: Negative Emissions, Spatiotemporal Fixes, and the Political Economy of Delay. Issue 3 (22nd March 2019) - Carton, Wim
Abstract: Models suggest that climate change mitigation now depends on negative emissions, i.e. the large‐scale removal of carbon dioxide from the atmosphere. This assumption has been criticised in the climate policy literature for being unfeasible and unjust. This article asks how critical scholars can make sense of, and contribute to these debates. It suggests that negative emissions can be conceived of as a spatiotemporal fix that promises to defer the devaluation of fixed capital. But the negative emissions example also challenges us to broaden our conception of how the socioecological contradictions of capitalism can be "fixed". I outline three ways in which it does this by highlighting the significance of a predominantly temporal fix, the role of hegemonic, sociopolitical interventions involving multiple actors, and the possibility of safeguarding existing production processes. I conclude that spatiotemporal fixes to climate change should be seen as part of a wider political economy of delay in devaluing carbon‐intensive accumulation processes.